2006
DOI: 10.1021/ac0608218
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Dopamine in Vivo by Microdialysis Sampling and On-Line CE-Laser-Induced Fluorescence

Abstract: Microdialysis sampling was coupled on-line to micellar electrokinetic chromatography (MEKC) to monitor extracellular dopamine concentration in the brains of rats. Microdialysis probes were perfused at 0.3 microL/min and the dialysate mixed on-line with 6 mM naphthalene-2,3-dicarboxaldehye and 10 mM potassium cyanide pumped at 0.12 microL/min each into a reaction capillary. The reaction mixture was delivered into a flow-gated interface and separated at 90-s intervals. The MEKC separation buffer consisted of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 49 publications
6
106
0
Order By: Relevance
“…Testing this system in a biological context, the authors were able to quantify the concentration of dopamine in a rat brain dialysate as 10 nM, a figure which agreed with previously reported values [35,69]. Moreover, upon adding a dopamine reuptake inhibitor to the sample, dopamine was released from the transporting proteins.…”
Section: Specific Dopamine Sensingsupporting
confidence: 81%
“…Testing this system in a biological context, the authors were able to quantify the concentration of dopamine in a rat brain dialysate as 10 nM, a figure which agreed with previously reported values [35,69]. Moreover, upon adding a dopamine reuptake inhibitor to the sample, dopamine was released from the transporting proteins.…”
Section: Specific Dopamine Sensingsupporting
confidence: 81%
“…Many self-administration studies have applied the equation to estimate brain concentrations of cocaine in live animals (Ahmed and Koob, 2005;Samaha et al, 2002;Zernig et al, 2007;Zimmer et al, 2011), and the equations have also been applied in studies using electrophysiology (Nicola and Deadwyler, 2000;Peoples and Cavanaugh, 2003;Peoples et al, 2004Peoples et al, , 2007, microdialysis (Wise et al, 1995) and voltammetry (Hermans et al, 2008;Stuber et al, 2005a, b). These studies have demonstrated that the modeled brain-cocaine concentrations are highly correlated with NAc dopamine levels (Hermans et al, 2008;Shou et al, 2006;Wise et al, 1995) as well as cocaine-induced locomotor behavior (Shou et al, 2006).…”
Section: Figurementioning
confidence: 99%
“…Recently, 4-fluoro-7-nitro-2,1,3-benzoxadiazole (NBD-F) was used as a fluorogenic label for the online, high-speed microdialysis-CE analysis of amino acid neurotransmitters (29). Sixteen amino acids were identified and separated every 20 s with improved detection sensitivity.…”
Section: Processes Prior To Cementioning
confidence: 99%